Scenario for Assistance and Protection of Human Trafficking Victims in Colombia - Alarcón-Moreno, Nancy Edith (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Through semi-structured interviews with civil society organizations and a person who was a victim of forced labor this article evidences the achievements or deficiencies of the State to guarantee the restoration of the rights of victims of trafficking in persons. The results of this study corroborate that the assistanceand protection of victims is insufficient or comes too late and there are no clear guidelines and protocols to assist and protect people who have experienced other forms of exploitation different from sexual exploitation.